2021
DOI: 10.1007/s11845-021-02775-0
|View full text |Cite
|
Sign up to set email alerts
|

Upper extremity deep venous thrombosis prevalence in the NHS Grampian Medical Ambulatory clinic: diagnostic, therapeutic, and prognostic considerations in oncology patients

Abstract: Introduction Whilst upper extremity deep vein thromboses (UEDVT) account for approximately 5 to 10% of all cases of DVT, rigorous guidelines regarding diagnosis and management of presenting patients remain to be developed. The association of UEDVT with concurrent asymptomatic pulmonary embolism as well as the first presentation of malignancy deems essential rigorous research and clinical guideline development to ensure optimal patient care. Methods This re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…PICC-related DVT is a well-described and studied topic, and studies have shown that the incidence of DVT can range from 2.4% to 15%. 17,18 This lower rate of DVT in PICC patients may be secondary to patient factors (unlikely to have malignancy, average age in early 1950s, and most likely to be ambulatory) as well as mechanical factors (PICC for antibiotic use typically utilizes single lumen catheter; the duration is usually in the order of weeks). Unfortunately due to the limitations of the mechanism by which we can extract the data based on CPT code, we were unable to identify which complications were truly secondary to PICC placement.…”
Section: Discussionmentioning
confidence: 99%
“…PICC-related DVT is a well-described and studied topic, and studies have shown that the incidence of DVT can range from 2.4% to 15%. 17,18 This lower rate of DVT in PICC patients may be secondary to patient factors (unlikely to have malignancy, average age in early 1950s, and most likely to be ambulatory) as well as mechanical factors (PICC for antibiotic use typically utilizes single lumen catheter; the duration is usually in the order of weeks). Unfortunately due to the limitations of the mechanism by which we can extract the data based on CPT code, we were unable to identify which complications were truly secondary to PICC placement.…”
Section: Discussionmentioning
confidence: 99%
“…The main risk factors for deep vein thrombosis of the upper extremity (DVT-UE) are central venous catheter(CVC), peripherally inserted central venous catheters (PICC), and cardiac pacemakers [31]. Foreign bodies in the vascular system represent the most signi cant independent risk factor for DVT-UE [32].…”
Section: Indwelling Needlementioning
confidence: 99%
“…11-13 Recent literature suggests that the incidence of UE DVT may be higher in patients who are overweight, have cancer, or have recently had a peripherally inserted central catheter (PICC line) inserted to deliver life-saving medications to a patient. 14-16 Interestingly, UE DVT is also possible in younger throwing athletes due to interstitial trauma from the repetitive forces of throwing during baseball that resulted in an effort thrombosis. 17…”
Section: Introductionmentioning
confidence: 99%